Study on effectiveness of heavy metals removal through the biosorption process using eucheuma cottonii - Lim, Cheryn Shin Ching (2014)
The high concentration of heavy metals such as zinc, cadmium, iron and lead are found in industrial wastewater and will bring negative effect to human health like mental illness and blood disease. Therefore, treatment is very important to remove the high content of heavy metal in the water before using as drinking purpose. Absorption treatment is one of the wastewater treatments that remove the heavy metal by using biomass like seaweed. Therefore, a study is needed to investigate the relationship of seaweed and heavy metals in industrial wastewater. The objectives of this study are to determine the characteristics of the industrial wastewater and to investigate the effectiveness of seaweed in the removal of lead and cadmium. The tests that will be carried out are biochemical oxygen demand, chemical oxygen demand and removal of the heavy metals. The standard method used to determine for BOD is APHA 5210 B, HACH DR/2500 Spectrophotometer with Method 8000 is for COD and AAS for the concentration removal of heavy metals. The maximum removal of BOD were 17.95% for cadmium solution and 24.91% for lead solution while the maximum percentage removal of COD were 58.9% for cadmium solution and 58.73% for lead solution. The concentration of the heavy metals such as lead and cadmium was removed by the process of biosorption using Eucheuma Cottonii: From the result of AAS, the concentration of the heavy metals reduced compare to the concentration before biosorption process. 77.9% of lead was removed from the lead solution and 62.96% of the cadmium was adsorbed from the synthetic solution after 30 hours. As a conclusion, the amount of the Eucheuma Cottonii will affect the effectiveness of the BOD, COD and heavy metals removal therefore seaweed can be used to treat the wastewater that released by industries.